Influence of Access Cavities on Maxillary Central Incisor Fracture Resistance: Finite Element Study - Yujiang Liu; Xinyao Huang; Haoyu Ke; Xinyi Song; Xinmeng Huang; Shufen Sun (Elsevier, 2024)
Introduction and aims: Altering the position and orientation of the root canal access cavity passway, or modifying the reduction of dentin volume, can influence the strength of dentition. This study aimed to compare the effects of different access cavities on the biomechanical performances of maxillary central incisors with a finite element analysis. Methods: Based on the micro-computed tomography (CT) scan of a maxillary central incisor, the finite element models of the intact tooth and teeth with 4 access cavity designs: conservative incisal access cavity, incisal access cavity, conservative access cavity, and traditional access cavity were generated. Simulated occlusal forces were applied at the incisal edge of the incisor in the finite element analysis procedure. Results: The maximum von Mises stress and maximum principal stress in the cervical area are highest in the traditional access cavity group, followed by the conservative access cavity group, incisal access cavity group, and conservative incisal access cavity group. Conclusion: The conservative access cavities minimise the extent of dentin removal from the cervical region, protecting the mechanical behaviour of the incisor. Moving the access cavity entry point to the incisal edge also improves the fracture resistance of the incisor. Clinical Relevance: This study's findings would help clinicians select the most appropriate endodontics access cavity method when performing the root canal on maxillary central incisors.